The limits of capacity building for investment contract negotiations - Karl P. Sauvant; Vanessa S. W. Tsang; Louis T. Wells (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Efforts to build specialized skills in government for negotiating international investment contracts often have little value for reasons discussed in this Perspective; even private firms hire advisors for skills needed infrequently. However, the Perspective proposes special circumstances and broader topics for which capacity building is likely to be useful.
Keywords: 330